2014
DOI: 10.3109/00016489.2014.923114
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of hearing loss in patients with unilateral Ménière’s disease

Abstract: In the PPH group, the hearing levels at the initial visit at middle and high frequencies were significantly worse than those in the GPH group. Moreover, the hearing loss progressed during the first 2 years of the disease, and stayed flat to approximately 50 dB at the later stage. Conversely, the hearing loss at the onset in the GPH group showed no further progression over the first 2 years, and remained constant to approximately 35 dB at the later stage. In addition, the mean intervals from the onset to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In terms of hearing prognosis, a compromised hearing ability at the initial visit may augur ill for the future in patients with Ménière's disease. 21 Sato et al 21 also found that the hearing levels at the initial visits were significantly worse in patients with poor than in those with good prognoses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In terms of hearing prognosis, a compromised hearing ability at the initial visit may augur ill for the future in patients with Ménière's disease. 21 Sato et al 21 also found that the hearing levels at the initial visits were significantly worse in patients with poor than in those with good prognoses.…”
Section: Discussionmentioning
confidence: 98%
“…In a retrospective study on 243 patients with Ménière's disease by Havia et al, 20 prolonged disease was associated with deterioration of hearing function. In a very recent study by Sato et al, 21 potential factors in connection with the prognosis of hearing loss were examined retrospectively in a group of 36 patients with unilateral Ménière's disease. They reported that the mean interval from the onset of the disease to the initial visit was significantly longer in patients with poor hearing.…”
Section: Discussionmentioning
confidence: 99%
“…One of the prognostic factors that affects hearing function is duration of the disease [33]. It is documented by most of the authors [34][35][36]. Age is also an independent prognostic factor to determine hearing function and its responsiveness to medical treatment [37].…”
Section: Hearing Lossmentioning
confidence: 99%
“…Tootoonchi et al reported improvement of 6.35 dB in hearing levels after 6 months of betahistine administration [37]. However, patient's first hearing levels should be considered; if the patient has poor hearing levels at the first visit, he is less likely to benefit from the treatment [36]. Cochrane reviews support the positive effect of betahistine on vertigo attack frequency and hearing levels.…”
Section: Betahistinementioning
confidence: 99%